2023
DOI: 10.21203/rs.3.rs-2566925/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards high-performance p-type two-dimensional field effect transistors: contact engineering, scaling, and doping

Abstract: N-type field effect transistors (FETs) based on two-dimensional (2D) transition metal dichalcogenides (TMDs) like MoS2 and WS2 have come closer to meeting the requirements set forth in International Roadmap for Devices and Systems (IRDS). However, p-type 2D FETs are dramatically lagging behind in meeting performance standards. Here, we adopt a three-pronged approach that includes contact engineering, channel length (Lch) scaling, and monolayer doping to achieve high-performance p-type FETs based on synthetic W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…In contrast, Cr/Au contacts on few-layer WSe 2 exhibit n-type transport while the vdW Pt contacts show p-type-dominant behavior. 19 This result is consistent with previous studies showing that vdW contacts are effective in achieving p-type transport in WSe 2 . 15,20 In addition, temperature-dependent transport measurements showing stable transport behavior over a large temperature range are shown in Figure S2.…”
supporting
confidence: 93%
“…In contrast, Cr/Au contacts on few-layer WSe 2 exhibit n-type transport while the vdW Pt contacts show p-type-dominant behavior. 19 This result is consistent with previous studies showing that vdW contacts are effective in achieving p-type transport in WSe 2 . 15,20 In addition, temperature-dependent transport measurements showing stable transport behavior over a large temperature range are shown in Figure S2.…”
supporting
confidence: 93%
“…However, most of the FETs mentioned above are n-type. Despite the development of p-type FETs, 17−20 current research on p-type FETs lags far behind that of n-type, 21 which greatly limits the development of complementary logical circuit transistors. 22,23 The monolayer FeOCl-type materials have attracted great attention because of their unique anisotropic structures.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Yoo and co-workers 24,25 recently reported that the p-doping of exfoliated WSe 2 was significantly enhanced by O 2 plasma treatment, an aging effect can be utilized to address the Fermi-level pinning (FLP) issue specifically related to metal/2Dsemiconductor contact, and electron beam irradiation can be employed to fine-tune the doping concentration induced by O 2 plasma treatment. Oberoi et al 26 achieved high-performance ptype conduction in a monolayer WSe 2 with O 2 plasma treatment of the CVD-synthesized bilayer in combination with contact engineering and channel length scaling.…”
Section: Introductionmentioning
confidence: 99%